Elsevier's dictionary of fishery, processing, fish and shellfish names of the world - Negedly, Robert (Elsevier Science, 1990)
Contained in this dictionary are terms and names arranged in alphabetical order covering the following areas: fisheries engineering, fishing methods, fishing vessels, deck equipment, fish processing, fish processing equipment, fish products, fish farming, inland fishery, fishery biology, ichthyology, names of crustaceans, moluscs and marine mammals. Language Notes: text: English ; original Language: French, Spanish, German, Latin.